A new 13N-complexity memory built-in self-test algorithm to balance static random access memory static fault coverage and test time - Jidin, Aiman Zakwan; Hussin, Razaidi; Mispan, Mohd Syafiq; Fook, Lee Weng (Institute of Advanced Engineering and Science, 2025)
As memories dominate the system-on-chip (SoC), their quality significantly impacts the chip manufacturing yield. There is a growing need to reduce the chip production time and cost, which mainly depends on the testing phase. Hence, a memory built-in self-test (MBIST) utilizing a low-complexity, high-fault-coverage test algorithm is essential for efficient and thorough memory testing. The March AZ1 algorithm, with 13N complexity, was created earlier to balance the test length and fault coverage. However, poor positioning of a write operation in its test sequence caused the reduction of the transition coupling fault (CFtr) detection. This paper presents the creation of the March AZ algorithm, modified from the March AZ1 algorithm, to increase CFtr coverage while preserving the same complexity. It was accomplished by analyzing the fault coverage offered by the March AZ1 algorithm and then reorganizing its test sequence to address the limitation in detecting CFtr. The newly produced March AZ1 algorithm was successfully implemented in an MBIST controller. The simulation tests validated its functionality and demonstrated that the CFtr coverage was enhanced from 62.5% to 75%, achieving an overall fault coverage of 83.3%. Therefore, with 13N complexity, it offers the best fault coverage among all the existing test algorithms with a complexity below 18N.